Optimal Online Configuration and Load-Sharing in a Redundant Electric Power System for an Offshore Vessel Using Mixed Integer Linear Programming - Thorat, Laxminarayan; Skjetne, Roger (Volume 1: Offshore Technology, 2018)
This paper proposes several schemes for optimal online configuration and load sharing for a shipboard power system of a typical offshore vessel, having a number of varying capacity gensets. Different methods are presented for optimal online scheduling and minimization of specific fuel oil consumption using mixed integer linear programming. The simulations for optimization of specific fuel oil consumption for three different scheduling methods demonstrate their properties. acceptedVersion Copyright © 2018 by ASME